El buen trato escolar y la autoestima en niños de la Institución Educativa Inicial N° 362, Yavarí 2022 - Castillo Flores, Gresely (2023)
The main objective of this research was to establish the relationship between good school treatment and self-esteem in children of the Initial Educational Institution No. 362 Yavarí 2022. The methodological approach originally used was modified, which consisted of a non-experimental, descriptive and correlational, by a descriptive, correlational cross-sectional design. The studied population included 74 children and their parents, and a census sample was selected. For data collection, survey and observation techniques were used, as well as an observation guide as an instrument. The instruments were validated by expert judgment. The results of the hypothesis test of the relationship and association between good school treatment and self-esteem were produced. The results indicated a low connection between both variables (r = 0.038). Consequently, the research hypothesis could not be supported, and the null or alternative hypothesis is accepted, which indicates that there is no connection between good school treatment and self-esteem in children of the Initial No. 362 Yavarí 2022.